“Check Your Network Connection”: Cyberpunk Visions of Disembodied Labor in Sleep Dealer - Michael Pitts (European Journal of American Studies)
The economic and social dimensions of the Mexico-U.S. border make up a topic frequently discussed within the field of North American Studies. Such studies typically concern the exploitative labor and immigration policies of the United States, which negatively shape the experiences of Mexican laborers crossing the border in search of better wages and work opportunities. Such research, however, often overlooks the power of cultural products such as film to comment upon these topics. As the following analysis of the Mexican film Sleep Dealer (2008) illustrates, film and, more specifically, cyberpunk cinema act as important vehicles through which complex commentaries on the socioeconomic conditions of the Mexico-U.S. border may be developed and presented.